Availability and occurrence of coelenterazine in a Swedish fjord to maintain Amphiura filiformis bioluminescence - Constance Coubris; Khaled Mirzaei; Laurent Duchatelet; Jérôme Mallefet (Scientific Reports)
Abstract The bioluminescent European brittle star Amphiura filiformis produces blue light at the arm-spine level thanks to a biochemical reaction involving coelenterazine as substrate and a Renilla-like luciferase as an enzyme. This echinoderm light production depends on a trophic acquisition of the coelenterazine substrate. Without an exogenous supply of coelenterazine, this species loses its luminous capabilities. Moreover, this species was recently shown not to produce coelenterazine storage forms. As an infaunal suspensive feeder, A. filiformis is assumed to find enough substrate to maintain its bioluminescence capabilities efficiently. To date, no studies have investigated the putative source of coelenterazine in the brittle star diet. A combined analysis using listing based on visual observations and metabarcoding on the planktonic communities highlights planktonic species known as light emitters using coelenterazine. Besides, the A. filiformis stomach content was analyzed seasonally via metabarcoding technique, and coelenterazine-related preys were underlined. Results provide evidence of the presence of preys containing coelenterazine in the fjord environment and within the stomach content of the ophiuroid throughout the year. The results are consistent with the demonstration of the trophic acquisition of luminous capabilities in A. filiformis and give a new step by underlying the constant presence of coelenterazine suppliers throughout the year for the luminescence reaction occurring within this species.